Water quality in small-scale coffee production units, Amazonas, Peru - Morales Rojas, Eli (2022)
The objective of this research was to determine water quality in small-scale coffee production units in the Amazon Region, Peru. The characterization of the factors associated with coffee farmers was collected through surveys. The Standard Methods for the Examination of Water and Wastewater (APHA) method was used to determine the physicochemical and microbiological parameters of the incoming water (AE) (water for human consumption) and the outgoing water (AS) (wastewater from coffee washing). The results indicated that the coffee growers do not have adequate technology for washing the coffee and that they use water for these activities. In the characterization of the water, significant differences were found between the parameters of the AE and the AS, where the pH of the AE ranged from 7.00 to 7.32 and the pH of the AS from 3.76 to 4.44. The turbidity of the AS showed high values of 1814.47 NTU. Total Coliforms (TC) and heavy metals such as copper and chromium all increased in value up to 0.20 and 0.15 ppm in the AS compared to the AE. The characteristics of the water quality consumed by the coffee growers are poor and values above Peruvian standards were found.